2020
DOI: 10.2298/tsci180810346a
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of natural convection and entropy generation in 3-D cavity with active lateral walls

Abstract: Numerical simulation of the natural convection and entropy generation in an airfilled cubical cavity with active lateral walls is performed in this work. Both the lateral front and right sidewalls are maintained at an isothermal cold temperature. While an isothermal hot temperature is applied for both the lateral back and left sidewalls. The upper and lower walls are kept adiabatic. Entropy generation rates due to the fluid friction and the heat transfer are simulated by using the Second law of thermodynamics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Spizzichino et al [17] enclosure was cold including cold and hot vertically aligned cylinders. Alnaqi et al [18] cavity with lateral active walls, the vertical front and right walls kept cold. While the vertical back and left were hot.…”
Section: Introductionmentioning
confidence: 99%
“…Spizzichino et al [17] enclosure was cold including cold and hot vertically aligned cylinders. Alnaqi et al [18] cavity with lateral active walls, the vertical front and right walls kept cold. While the vertical back and left were hot.…”
Section: Introductionmentioning
confidence: 99%
“…Systems can be optimized by reducing their entropy generation. Alnaqi et al (2020) studied the natural convection and entropy generation in a cubical cavity and observed that total entropy fairly increased with an increase in Rayleigh number until a certain value, when it then rose significantly. Similar studies have also been carried out (Bondareva et al, 2017;Hussein et al, 2016;Yang et al, 2021;Zhang et al, 2021;Ishak et al, 2021;Oztop et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the angle of inclination has an insignificant effect with respect to low Rayleigh numbers. Alnaqi et al 26 examined numerically laminar natural convection and entropy generation in a 3D cubical cavity with active perpendicular walls. They revealed that with increasing the Rayleigh number until reaching a value of 10 5 , heat transfer and total entropy generation increased slightly.…”
Section: Introductionmentioning
confidence: 99%